RECENT INNOVATIONS IN MICROFABRICATION TECHNIQUES FOR ENHANCED MICROFLUIDIC CHIP PERFORMANCE IN DRUG DEVELOPMENT - ROY, ANKANA; SG, VASANTHARAJU; BS, MUDDUKRISHNA; ERANTI, BHARGAV; PAWAR, SACHIN DATTRAM; RAVI, GUNDAWAR (International Journal of Applied Pharmaceutics, 2025)
An example of a mobile laboratory is microfluidic chip technology or lab-on-a-chip. It is one of the great breakthroughs in the pharmaceutical industry as it allows flexibility in controlling experiment conditions, minimizing sample and reagent waste, and allowing high-throughput screening. Microfluidics has roots in molecular analysis, microelectronics, biodefense, and even molecular biology; likewise, gas-phase chromatography and capillary electrophoresis are ancestors for it. Determining the use of this equipment in laboratories leads to automation, miniaturization of procedures, precision and uncertainty in drug creation, and repeatable experiments, which enhances the accuracy of results. Its merits are the performance of computerized simulation of organs, where it enhances the drug screen, toxicity testing, personalized medicine, and pharmacokinetics, which leads to the testing of thousands of candidate drugs being tested at once. Its performance is excellent; however, it cannot be denied that it has a disadvantage, which is in designing the chip and integrating it with the already existing system. It has yet to integrate widely used markers for patient samples and other markers to improve point-of-care diagnostics that aim to use the patient’s sample to work on to change the structure of future studies in the pharmaceutical industry.